PEMBELAJARAN TEKNIK DASAR LOMPAT JAUH MELALUI PERMAINAN RANGKAIAN 3 POS PADA SISWA KELAS V SD NEGERI BUMIJAWA 07 KECAMATAN BUMIJAWA KABUPATEN TEGAL TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
The purpose of to know how the application of learning basic techniques long jump through a series of threeposts on the game fifth grade elementary school students Bumijawa 07. To obtain the appropriate data in thisstudy using PTK (Classroom Action Research). For TOD shaped cycle assessment process, which consists offour stages: planning, action, observation and reflective. The research instrument using the check list to recordthe attitudes and events that occur in learning deemed important and have been set will be investigated.From the observations obtained with the help of a check list can be obtained that the percentage of cognitiveabilities, affective and psychomotor of fifth grade elementary school students Bumijawa Bumijawa TegalDistrict 07 before the research is 71%, 75.5%, and 68%. After being given an increase in learning, first learningof cognitive skills increased to 75.5%, 78.25% affective abilities, and psychomotor abilities 73.13%. Becausethere are aspects that have not reached mastery, then held a 2 cycle. After the second lesson, otherwisecompleted all aspects of the cognitive 81%, 79.75% affective, and psychomotor 76.88%. Conclusions from thisresearch is through learning approach Penjasorkes 3 game series heading to improve learning outcomes ofstudents achieving mastery learning for all aspects of the cognitive, affective, and psychomotor.learning the basic techniques of the game long jump through a series of 3 posts to enhance student learning inelementary school students learning Penjasorkes